Investigating the water balance of on-farm techniques for improved crop productivity in rainfed systems: A case study of Makanya catchment, Tanzania - Makurira, H.; Savenije, H.H.G.; Uhlenbrook, S.; Rockström, J.; Senzanje, A. (Physics and chemistry of the earth. Parts A/B/C, 2009)
Water scarcity is a perennial problem in sub-Saharan agricultural systems where extreme rainfall events dominate agricultural seasons. Dry spell occurrences between and during seasons negatively impact on crop yields especially if such dry spells exceed 14 days. The impact of dry spells is felt more at smallholder farming scales where subsistence farming is the only source of livelihood for many households. This paper presents results from on-going research to improve rainfed water productivity in arid and semi-arid regions. The study site is the Makanya catchment in northern Tanzania where rainfall rarely exceeds 400 mm/season. Rainwater alone is not sufficient to support maize which is the preferred crop. The research introduced new soil and water conservation measures to promote water availability into the root zone. The introduced techniques include deep tillage, runoff diversion, fanya juus (infiltration trenches with bunds) and infiltration pits. The research aims at understanding the effectiveness of these interventions in increasing moisture availability within the root zone. Time domain reflectometry (TDR) was used to measure soil moisture twice weekly at 10 cm depth intervals up to depths of 2 m. Soil moisture fluctuated in the range 5–25% of volume with the beginning of the season recording the driest moisture levels and periods after good rainfall/runoff events recording the highest moisture levels. From the field observations made, a spreadsheet model was developed to simulate soil moisture variations during different maize growth stages. The results obtained show that the zones of greatest soil moisture concentrations are those around the trenches and bunds. Soil moisture is least at the centre of the plots. The study confirms the effectiveness of the introduced techniques to help concentrate the little available rainfall into green water flow paths. Indirect benefits from these improved techniques are the creation of fertile and moist zones around the bunds where supplementary food crops (e.g. bananas and cassava) can be grown even in dry seasons.